Análisis de las reformas laborales y su influencia en la empleabilidad y producción en la empresa pasteurizadora El Ranchito CIA. LTDA. Período 2014. Diseño de una propuesta a las reformas laborales. - Salazar Tipantásig, Germánico (2015)
This research was aimed to analyze the various reforms in labor legislation and employability Ecuador has had in the last period 2014. Throughout history the country has been the focus of several constitutional and labor reforms, incorporating concepts and clauses in favor of workers, so, from the creation of 13 the new Constitution of the Republic of Ecuador in 2008, new key concepts and reformatories are incorporated in the country, which help boost employment, however , outsourcing and all forms of precarious employment in enterprises was also eliminated, working 8 hours a day, with the constitutional mandate No. 8. The subject matter and scope were workers of the company "El Ranchito", were surveyed to such workers in order to expose and compare data with previous studies and demonstrate and evaluate the changes that have existed.